GOVERNANCE: A PROCUREMENT PERSPECTIVE - Kian Peng, Yeo; Ken (The journal of contemporary issues in business and government, 2008)
Substantial attention has recently been given to governance and internal control systems of organisations, particularly in the procurement environment. Poor governance has, in the past, led to several major corporate collapses and, on a smaller scale, poor governance or inadequate internal control processes has resulted in fraud and pilferage. Although there are many avenues for organisations to reprimand the perpetrators, punishment is often insubstantial or nonexistent. This article investigates the factors fostering such fraudulent behaviour and the resources available for deterring these acts. It will also explore the various stages of procurement—contract planning, formation and management—and suggest how organisations can use procurement as a tool to improve governance.